Numerical Literacy Skills of Vocational High School Students in Solving HOTS Problems - Nurokhmi Wahyu Setiani; Mohammad Asikin; Nuriana Rachmani Dewi (AlphaMath : Journal of Mathematics Education, 2022)
This study aims to describe the numeracy literacy skills of Vocational High School (SMK) students in solving High Order Thinking Skills (HOTS) problems. The type of research used is descriptive qualitative research. Sampling was done by purposive sampling technique. This research was conducted at SMK Komputama Jeruklegi in XI TKJ 1. Data collection used a numeracy literacy test and interview guidelines. The results showed that students answered correctly on indicator 1 of numeracy literacy by 37.7%; indicator 2 by 31.9%; and indicator 3 by 27.2%. If viewed based on the percentage of each category of HOTS questions, the correct answer in the C4 category (analyze) is 33.9%; category C5 (evaluate) by 28.3%; and category C6 (create) by 32.6%. Based on these results, it shows that students' numeracy literacy skills are still low in solving questions in the HOTS category. The results of this study serve as a reference for teachers and schools to implement more effective and innovative learning so as to improve students' skills in solving problems with higher-order thinking categories. Besides that, it can also be used as a consideration for teachers and students in implementing learning that can foster students' literacy skills.